2009
DOI: 10.1080/08880010902754826
|View full text |Cite
|
Sign up to set email alerts
|

Altered Iron Metabolism in Children With Human Immunodeficiency Virus Disease

Abstract: These data indicate that alterations in iron metabolism are common even in the HAART era and warrant further study to identify individuals at risk for these alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…31 Iron deficiency is highly prevalent (18.0-44.3%) in developing countries, 3,29 but not in this study. The high prevalences of IDA in other studies might be the result of the inclusion of children with poorer nutritional status and more severe clinical stage of HIV.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…31 Iron deficiency is highly prevalent (18.0-44.3%) in developing countries, 3,29 but not in this study. The high prevalences of IDA in other studies might be the result of the inclusion of children with poorer nutritional status and more severe clinical stage of HIV.…”
Section: Discussionmentioning
confidence: 83%
“…32 Serum ferritin is an acute phase reactant that may be increased in chronic inflammatory diseases such as HIV infection. 31,33 High levels of serum ferritin have been reported in AIDS patients; the more advanced the stage of disease, the higher the serum ferritin level. 34 However, in this study, we enrolled HIV-infected children with moderate immunosuppression, with a generally low incidence of opportunistic infections, and excluded children with acute illness.…”
Section: Discussionmentioning
confidence: 99%
“…The above suggestions are certainly true of infections caused by influenza A (Visseren et al 2002) (see also Akaike et al 1996; Beck et al 2004), herpes simplex virus (Gennero et al 2010; Lamey and Biagioni 1995; Romeo et al 2001), hepatitis C (Alavian and Tabatabaei 2009; Alla and Bonkovsky 2005; Ameli et al 2008; Bassett 2007; Batts 2007; Bonkovsky 2002; Bonkovsky et al 2006; Desai et al 2008; Di Marco et al 2008; Drakesmith and Prentice 2008; Fargion et al 2002; Ferrara et al 2009; Franchini et al 2008; Fujita et al 2007a, b; Fujita and Takei 2007; Girelli et al 2009; Gürkan et al 2005; Guyader et al 2007; Hayashi and Yano 2002; Heathcote 2004; Kaito 2007; Kaito et al 2006; Kato et al 2001, 2007; Ko et al 2007; Mahmoud et al 2008; Mueller et al 2006; Nahon et al 2008; Nishina et al 2008; Otogawa et al 2008; Price and Kowdley 2009; Rigamonti et al 2005; Sebastiani and Walker 2007; Sikorska et al 2010; Sugimoto et al 2009; Tanaka et al 2007; Tanaka and Kiyosawa 2004; Trinder et al 2008; Tung et al 2003; Valenti et al 2008; Venturini et al 2010; Won et al 2009) and HIV (Boelaert et al 1996; Butensky James et al 2009; de Monyé et al 1999; Debebe et al 2007; Drakesmith and Prentice 2008; Georgiou et al 2000; Gordeuk et al 2001, 2006; Kagu et al 2007; Ketonen et al 1996; McDermid et al 2007; McDermid and Prentice 2006; McDermid et al 2009; Meyer 2006; Northrop-Clewes 2008; Rawat et al 2008; Savarino et al 1999; Schreck et al 1992; Szajerka and Jablecki …”
Section: Virusesmentioning
confidence: 99%
“…Clinical and experimental evidences have indicated that the metabolism of iron is altered in HIV‐patients and that several steps in the HIV‐1 replicative cycle require iron [Traoré and Meyer, ; James et al, ; Rawat et al, ; Nekhai et al, ]. In HIV‐patients, iron deficiency is common and elevated iron stores are associated with faster disease progression.…”
Section: Introductionmentioning
confidence: 99%